Anti-SRP antibody-associated necrotizing myopathy: 2 clinical cases - F. A. Abbasov; G. V. Zemtsova; P. A. Popov; K. I. Chekhonatskaya; D. V. Kukhno; M. M. Severova; M. V. Shmyreva; A. A. Kindarova; D. Yu. Schekochikhin (Нервно-мышечные болезни)
Necrotizing myopathies are a subtype of autoimmune myopathies characterized by muscle fiber necrosis with minimal infiltration by inflammatory cells on muscle biopsy. This group of myopathies is defined by flaccid palsies due to prima‑ ry skeletal muscle damage as well as extramuscular manifestations such as fever, rash, arthritis, Raynaud’s syndrome and interstitial lung disease. The presence of anti-SRP antibodies is associated with rapidly progressive refractory myositis predominantly affecting limb muscles and axial muscles.Objective of the work is to analyze the course of severe, refractory to several lines of immunosuppressive therapies anti-SRP associated necrotizing myopathy and to highlight an adequate treatment regime.Necrotizing myopathy was suspected in patients aged 39 and 56 years with rapidly progressive flaccid tetraparesis on the basis of clinical and anamnestic data, the results of needle electromyography and muscle magnetic resonance imaging, as well as the analysis of myositis-specific and myositis-associated autoantibodies. In both cases, a rapid development of atrophies, marked muscle weakness in the limbs, without involvement of the bulbar musculature, was observed. To achieve effective control of the disease progression, several lines of therapy were required: glucocorticosteroids, intravenous immunoglobulins, methotrexate and rituximab. Our observations are consistent with those in the literature.Our observations illustrate the clinical course of severe myopathy associated with anti-SRP antibodies. Early initiation of aggressive immunosuppression is crucial to control the disease progression. Treatment and rehabilitation allow achieving significant improvement of the patient’s condition.